PERENCANAAN SISTEM PENYEDIAAN AIR MINUM (SPAM) KECAMATAN KAPUR IX KABUPATEN LIMA PULUH KOTA - Budi Andri; Surya Eka Priana; Ana Susanti Yusman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The need for drinking water is increasing. In order to achieve a balance between water demand and water availability in the future, this research was conducted in Kapur IX District. The water source used is bulk water. The amount of water availability is calculated using three methods, namely: Geometric Method, Arithmetic Method and Potential Method. The raw water sources used are Batang Simonok and Lubuak Sati waters with a flow rate of 40 liters/sec. And the results of Labor testing can meet the requirements of the Minister of Health RI No. 416/1990 with 24 hour serviceKeywords: Drinking Water Needs, Capacity, Reservoir